The functional significance of the G to A point mutation in the promoter region of the Apolipoprotein AI gene - Wells, Carol Dawn (Division of Medical Biochemistry and Structural Biology, 2018)
AG to A transition at position -76 in the promoter region of the apoAI gene was previously identified, and the A-76 has been shown to be associated with high apoAI levels. The functional significance of the point mutation was assessed by analysing the DNA-protein binding and promoter activities of the different alleles. This data would suggest that the point mutation alters the function of the apoAI promoter as gel retention assays revealed that the G fragment (-140 to +10) formed an extra DNA-protein complex compared to the A fragment (-140 to +10). Concurrent with the altered DNA-protein interaction between the G and the A fragments, the transcriptional activities of the apoAI gene were found to also be altered. CAT assays have indicated a 1.91 fold increase in promoter activity of the A fragment as compared to the G fragment (-256 to +397). The difference in promoter activity was, however, highly dependent on the particular fragment used, as no difference was observed between the alleles when a fragment {-256 to +68) was used. In this study elements were identified in the region +68 to +397 that causes a reduction in the promoter activity of the G allele by 3.6 fold, whilst reducing the A allele activity by 2 fold. This data would suggest that the point mutation functionally alters the apoAI promoter activity via its interaction with other sequences especially in the region +68 to +397.